Anapole mediated giant photothermal nonlinearity in nanostructured silicon - Tianyue Zhang (Nature Portfolio, 2020)
Here, the authors report large photothermal nonlinearity mediated by anapole states within subwavelength Si nanodisks, offering a mechanism for dynamic tuning of far-field radiation from multipolar modes. Nonlinear scattering is used to demonstrate the potential for far-field optical localization of Si nanostructures.